2019
DOI: 10.1186/s40623-019-1072-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric wind variations observed by a Fabry–Perot interferometer at Tromsø, Norway, at substorm onsets

Abstract: Energy input from the magnetosphere during substorms can strongly affect the high-latitude thermosphere. The ionospheric current caused by thermospheric wind variations may also provide a feedback to the magnetosphere. In this study, we investigate the characteristics of high-latitude thermospheric wind variations at local substorm onsets at Tromsø, Norway, as well as the possibility of such feedback mechanism. A Fabry-Perot interferometer (FPI) at Tromsø provided wind measurements estimated from the Doppler s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Cai et al, 2019;Ritter et al, 2010;Xu et al, 2019;Zou et al, 2018Zou et al, , 2020. Ritter et al (2010) and Xu et al (2019) both reported fairly small wind variations (no more than a few tens m/s) after substorm onset, and the deviation tends to be eastward in the premidnight sector, yet Cai et al (2019) and Zou et al (2020) both noticed the presence of much larger (>100 m/s) variation magnitudes with westward/southward wind intensification. One of the possible reasons for the above discrepancy might be the difference in the observation latitudes relative to substorm-intensified auroras.…”
Section: Summary Of Two Steve Eventsmentioning
confidence: 99%
“…Cai et al, 2019;Ritter et al, 2010;Xu et al, 2019;Zou et al, 2018Zou et al, , 2020. Ritter et al (2010) and Xu et al (2019) both reported fairly small wind variations (no more than a few tens m/s) after substorm onset, and the deviation tends to be eastward in the premidnight sector, yet Cai et al (2019) and Zou et al (2020) both noticed the presence of much larger (>100 m/s) variation magnitudes with westward/southward wind intensification. One of the possible reasons for the above discrepancy might be the difference in the observation latitudes relative to substorm-intensified auroras.…”
Section: Summary Of Two Steve Eventsmentioning
confidence: 99%
“…(2010) and Xu et al. (2019). The amplitude of the wind variations, however, is on the order of ∼200 m/s, much more significant than seen by Ritter et al.…”
Section: Introductionmentioning
confidence: 96%
“…The plasma convection driven by MHD processes in the magnetosphere can cause associated neutral wind in the thermosphere through ion-neutral collision (e.g., Conde et al 2001;Xu et al 2019). The auroral particles and associated Joule heating also cause disturbances in the high-latitude thermosphere (e.g., Lu et al 2016).…”
Section: Connection From the High-latitude Energy Input To The Thermomentioning
confidence: 99%